Analisis Laporan Keuangan dengan Metode Trend Analysis untuk Mengevaluasi Kinerja Keuangan pada PT. Aneka Tambang Tbk Periode Tahun 2021-2023 - Armel, R. Septian; Yudisthira, Randi; Raza, Sania; Putra, Barnard Defano; Zahira, Tengku Jihan; Aulia, Rizka; Gunawan, Rika; Rahmadini, Wan Karin; Sari, Ocha Widya Sari (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to analyze the financial statements of PT. Aneka Tambang Tbk (antam), which is a company operating in the mining sector. PT. Aneka Tambang Tbk focuses on exploration, processing, mining and marketing of natural mineral commodities such as gold, bauxite and nickel. This research uses secondary data obtained from company annual reports and also financial reports published on the Indonesia Stock Exchange. This research was conducted using trend analysis during the 2021-2023 period. Trend Analysis is used to evaluate significant changes in key aspects such as revenue, costs and profitability in a company's financial statements during that period. It is hoped that the results of this research will provide in-depth insight into the factors that have influenced the company's financial performance in recent years.